Reaktualisasi Kepemimpinan Perempuan dalam Korelasinya dengan Konsep Kepemimpinan Transformasional - Khalidiyah, Hasanatul; Khusnuridlo, Moh.; Zein, Hepni (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
The dominance of the connotative meaning of leadership and its impact on the role of women is the reason why this study of the actualization of women's leadership should be carried out. The functional side of the meaning of women which contains the implications of the concept of transformational leadership makes this study more worthy of research in the related literature. This is a literature study that tries to reveal the meaning of women's leadership and its correlation with the perspective of Bass and Reggio’s transformational leadership. Excavation of data through leadership literature and several reports of field observations. The analysis uses Miles and Hubarman's interactive analysis, namely: condensation, conclusion and verification. The results of this study include, first, the reinterpretation of women's leadership; second, a description of the functional correlation between leadership, women, and transformational terms; and third, the emergence of opportunity and sportsmanship of meaning and attitude as a product of the correlation.